The Power of Trust: Exploring Its Contribution to E-commerce Purchase Decisions - R. Nur Budi Setiawan; Andika; Danang Wahyudi; Ela Deliani (PT Inovasi Pratama Internasional, 2023)
This study aims to evaluate the effects of service quality, security, and price perception on consumer trust and purchasing decisions on Tokopedia. Additionally, this study also aims to examine the mediating role of consumer trust in the relationship between the variables of service quality, security, price perception, and purchase decisions. The research was conducted in Yogyakarta using the snowball sampling method to select a sample of Tokopedia customers. A total of 250 respondents participated in the study. Data collection was carried out through questionnaires using a Likert scale of 1-5. Data analysis was performed using the Partial Least Squares (PLS) method with Smart PLS 3.3.3 software. The results showed that the security variable and price perception significantly influenced consumer trust, while service quality had a significant negative relationship with purchasing decisions. However, the variables of service quality, security, and price perception did not have a significant influence on purchasing decisions. Consumer trust was found to mediate the effects of security and price perception on purchasing decisions, but it was unable to mediate the effect of service quality. Overall, Tokopedia needs to improve communication regarding service quality, ensure a high level of security, consider other factors that influence purchasing decisions, and continue to build consumer trust.